INFLUENCE OF AUXIN ON BIOMASS PRODUCTION AND WITHANOLIDE ACCUMULATION IN ADVENTITIOUS ROOT CULTURE OF INDIAN RENNET: WITHANIA COAGULANS - Murugesan, Parameswari; Senthil, Kalaiselvi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Withanolides are the biologically active, principle compound present in Withania coagulans, which is having a high medicinal value and possesses potent therapeutic activity. The present study was attempted with an objective to investigate a biomass growth and withanolide production in in vitro root tissues of W. coagulans. Methods: High-performance thin layer chromatography (HPTLC) often serves as a method for quantification of major withanolides. In the present study, methanolic withanolide extract of in vitro cultured W. coagulans root tissue were carried out using HPTLC. The HPTLC analysis was performed using precoated silica gel aluminum plate (20 cm × 20 cm) 60F254 (E.MERCK, Germany) with mobile phase toluene: ethyl acetate: formic acid (5:5:1). Results: The optimization of different combination and concentration of plant growth regulators (indole-3-butyric acid [IBA] and indole-acetic acid) was used to stimulate the biomass growth and withanolide production. The maximum biomass growth (7.48±0.25 g/dL) was observed in medium with 4.93 μM−1 IBA. The higher amount of withanolide A (204.98±0.87 μg/L DW) and withaferin A (227.15±0.57 μg/L DW) accumulation was recorded in culture grown on half Murashiga-Skoog media supplemented with 4.93 μM−1 and 2.46 μM−1 IBA. Conclusion: We concluded that in vitro-cultured system could provide unique opportunities for large-scale production of pharmaceutically important compound than field grown plants.